The burden, risk factors and prevention strategies for drowning in Türkiye: a systematic literature review - Ali Işın; Amy E. Peden (BMC, 2024)
Abstract Introduction Drowning is a public health problem in Türkiye, as in the rest of the world. This study aims to systematically review the literature on drowning in Türkiye with a focus on data sources, epidemiology, risk factors and prevention strategies. Methods: Literature searches were conducted using PubMed, SPORTSDiscus, Scopus, Web of Science, Turk MEDLINE, Google Scholar and Google Akademik (Turkish language). Studies (limited to original research written in English and Turkish) reporting drowning (unintentional and intentional; fatal and non-fatal) of residents and tourists in Türkiye were independently dual screened at the title and abstract and full text stages. Study quality was assessed using JBI checklists and evidence level assessed based on study design. Results: From a total of 917 studies, 49 met the inclusion criteria. Most (51%) focused on unintentional fatal drowning. Included studies were most commonly analytical cross-sectional studies (n = 23) and case series (n = 20) meaning the evidence level was low or very low for 48 (98%) studies. Fifteen studies examined drowning at the national level, while sub-national studies (n = 30) focused on urban areas across three provinces: Antalya (n = 6), Istanbul (n = 6), Izmir (n = 4). There was little consensus on risk factors beyond male drowning risk, and no data reported on implemented or evaluated drowning prevention interventions. Discussion: There is a need for more national-level studies to identify the causes of drowning and to guide intervention implementation and evaluation to inform policy makers and donors. Currently official data is limited in its detail, providing age and gender data only, hampering efforts to identify, and thus address, causal factors for drowning. Practical applications: There is currently very little evidence to inform investment in effective drowning prevention interventions in Türkiye. To improve this, data collection systems on drowning in Türkiye need to be strengthened via the development a national drowning registry. Trial Registration #CRD42022382615.